Epistemology - Norris, Christopher, 1947- (Key concepts in philosophy., 2005)
Christopher Norris attempts to make epistemology, the theory of knowledge, accessible to students and those with little prior knowledge of the subject through a series of debates which aim to give an balanced overview.